2021
DOI: 10.21203/rs.3.rs-537082/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiological associations with genomic variation in SARS-CoV-2

Abstract: The 2019 novel coronavirus (SARS-CoV-2) is the etiological agent of the COVID-19 pandemic and evolves to evade both host immune systems and intervention strategies. To diminish the short-term and long-term impacts of coronavirus (CoV), we investigated CoV differences at the nucleotide and protein level and CoV genomic variation associated with epidemiological variation and geography. We divided the CoV genome into 29 constituent regions for this analysis. Our results highlight the variation of CoV variants of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…We have shown that the SARS-CoV-2 genomic variation is independent of host characteristics (e.g., age and gender) 1 , and here as a next step, we investigated the factors that influence COVID-19 disease severity using an integrated approach involving analyses of metabolite and protein profiles, epidemiological data, and clinical data, previously published 2 . The measurements included a complete blood cell count panel, a comprehensive metabolic test panel, and quantification of 941 metabolites and 894 proteins from serum samples.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that the SARS-CoV-2 genomic variation is independent of host characteristics (e.g., age and gender) 1 , and here as a next step, we investigated the factors that influence COVID-19 disease severity using an integrated approach involving analyses of metabolite and protein profiles, epidemiological data, and clinical data, previously published 2 . The measurements included a complete blood cell count panel, a comprehensive metabolic test panel, and quantification of 941 metabolites and 894 proteins from serum samples.…”
Section: Introductionmentioning
confidence: 99%
“…Patients' saliva was sampled upon admission in most cases, but as the hospital resources were strained with a heavy influx of COVID-19 patients during that time, some patients were recruited 3 or more days after admission, when they had started treatment. While many COVID-19 studies have focused on epidemiological associations of SARS-CoV-2 8 and dynamics of microbiome during infection, CLAIRE (CLuster AI pREdiction of disease progression) is the only study to investigate the COVID-19 saliva microbiome in hospitalized patients with a focus on sepsis and broad-spectrum antibiotics. The SARS-CoV-2 virus was characterized through Illumina's Respiratory Viral Oligo Panel (RVOP) sequencing 9 .…”
Section: Introductionmentioning
confidence: 99%